"What happens in the field is crucial!" : Curricular and practical consequences of digitalisation and networking in agriculture - Bretschneider, Markus [Verfasser] (My University, 2019)
How are tasks and competencies in the agricultural sector changing as a result of digitalisation and networking, and how does vocational education and training need to react? On the basis of technology deployed, this article investigates the issue of how skills, knowledge and competencies are cur-rently changing in the recognised training occupation of farmer, and which requirements and consequences this is creating at the curricular and practical level. In light of the growing significance of process and system competencies and handling data, the teaching module “Information-based agricultural technology” will be used as an example to show how competencies relating to the systematic use of production data can be practically imparted and how trainers can be supported in their daily work. (Author's abstract ; BIBB-Doku)
"Entscheidend ist auf dem Feld!"
Keywords: S 6.1.1 Land-, Tier-, Forstwirtschaft und Gartenbau; Agrarberuf; Landwirt; Berufsausbildung; Digitalisierung; Kompetenzentwicklung